2009
DOI: 10.1002/jbt.20296
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in rat lung epithelial cells by multiwalled carbon nanotubes

Abstract: Carbon nanotubes (CNTs), the most promising material with unique characteristics, find its application in different fields ranging from composite materials to medicine and from electronics to energy storage. However, little is known about the mechanism behind the interaction of these particles with cells and their toxicity. So, here we investigated the adverse effects of multiwalled CNTs (MWCNTs) in rat lung epithelial (LE) cells. The results showed that the incubation of LE cells with 0.5-10 microg/mL of MWCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…In vitro studies reported various toxicological effects of MW-CNTs including oxidative stress, DNA damage and apoptosis in mammalian cells lines. Other effects include VE-cadherin distribution and actin filament integrity in human aortic endothelial cells [114][115][116][117][118].…”
Section: Effects On Cell Linesmentioning
confidence: 99%
“…In vitro studies reported various toxicological effects of MW-CNTs including oxidative stress, DNA damage and apoptosis in mammalian cells lines. Other effects include VE-cadherin distribution and actin filament integrity in human aortic endothelial cells [114][115][116][117][118].…”
Section: Effects On Cell Linesmentioning
confidence: 99%
“…Our earlier studies using different nanoparticles such as single and multi walled carbon nanotubes showed significantly increased levels of ROS at 5-10 µg/ml. [19][20][21][22], whereas, here in ZnO nanorods, we did not detect any increase in ROS level even in 20 µg/ml (data not shown). The time kinetics was also performed to check the formation of ROS (see Fig.…”
Section: Resultsmentioning
confidence: 49%
“…Also, 5 mM of ZnO nanoparticle are shown to be less toxic to human T cells [27]. Previous studies from our laboratory on hela cells and other cells such as lung epithelial, H1299, A549 and HaCaT cells showed the decrease in cell viability at 5 µg/ml when they were exposed to SWCNT and MWCNT [19][20][21][22].…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…104 Still, because of their fiber shape and size, carbon nanotubes cause cytotoxicity, inflammation, and DNA damage in vitro. [193][194][195][196] The animal models used to study the toxic effects of carbon nanotubes demonstrated that the high concentrations needed to induce the regression of the tumor may cause chronic lung inflammation, foreign-body granulomas, or interstitial fibrosis, [197][198][199][200] limiting their potential clinical use.…”
mentioning
confidence: 99%